Effects of Coupling Agent and Flame Retardant on the Performances of Oil Palm Empty Fruit Bunch Fiber Reinforced Polypropylene Composites - R., Ridzuan; Beg, M. D. H.; R. M., Yunus; S., Samahani; M. H., Rohaya; A. A., Astimar; I., Zawawi (2013)
Alkali treated oil palm empty fruit bunch (EFB) fibres (TEFBF) and untreated EFBF fibers (UEFBF) were incorporated in polypropylene (PP) with and without malic anhydride grafted PP (MAPP) and magnesium hydroxide as flame retardant (FR) to produce TEFBF-PP and UEFBF-PP composites by the melt casting method. The composites were characterized by mechanical and burning tests along with a scanning electron microscope and Fourier transform infrared spectroscopy. The significant improvement in flexural modulus (133%) and flame retardant property (60%) of TEFBF-PP composite with MAPP and FR is observed. The improved mechanical property is discussed by the development of encapsulated textures.